Quality of Instruction and Entrepreneurial Mindset of Business Studies Students at Upper-Basic Schools in Nigeria - Alao, Olusegun; Njoku, Christiana Chikodi; Hamzat, Azeezat Oluwatoyin; Omopariola, Bukola Victoria (Journal of Pedagogy and Education Science, 2024)
Despite the employability and self-employment goals and objectives of pre-vocational subjects outlined in the National Policy on Education, the prevailing incidence of unemployment among the youth and its attendant crises in Nigeria were significant concerns to stakeholders and society.  Therefore, this study sought to assess the quality of instruction in the Business Studies curriculum and students’ mindset for entrepreneurship and self-employment at public and private upper-basic schools in Lagos, Nigeria. Three research questions and three hypotheses guided the study. The study population comprised 4.435 students, all teachers of business studies subjects in the selected upper-basic schools in Lagos, Nigeria. Using simple random and proportional sampling techniques, the sample size was 467 students and 11 teachers. The research instruments used were a structured questionnaire and a checklist. The internal consistency of the research instruments, using the Cronbach Alpha reliability coefficient, yielded an average value of 0.72, which shows that the instruments were very reliable. Mean and standard deviation and t-tests were used as statistical tools at a 0.05 significance level. The findings show that the recommended experiential instructional strategies were not adequately implemented. Even though most respondents claimed to have a mindset for entrepreneurship and self-employment, many agreed that the quality of the Business Studies subject needs to improve for adequate employability and self-employment empowerment. Based on the findings, sufficient availability and functionality of the approved instructional resources and constant use of innovative instructional strategies were some of the recommendations.